2022
DOI: 10.37385/jaets.v4i1.1015
|View full text |Cite
|
Sign up to set email alerts
|

Smart Trash Bin for Management of Garbage Problem in Society

Abstract: Along with the times, one of the environmental problems faced today is the waste problem. Every day humans will produce waste, both industrial waste and household waste in everyday life. Garbage will become an environmental problem because it can interfere with human health, cause bad smells and even air pollution. Poor waste management causes harmful and unhealthy environmental problems. Sometimes people are reluctant when they want to dispose of garbage by opening and closing the trash can so it is feared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A forest fire detection system or forest alert applying the leading technology of the IoT is to find out the signs of forest or land fires faster. The application of IoT technology is needed in sending information to land owners and the Pekanbaru City BPBD [18], [19]. In addition, in distributing data to the server, the proposer utilizes cloud computing as data storage and distribution.…”
Section: Methodsmentioning
confidence: 99%
“…A forest fire detection system or forest alert applying the leading technology of the IoT is to find out the signs of forest or land fires faster. The application of IoT technology is needed in sending information to land owners and the Pekanbaru City BPBD [18], [19]. In addition, in distributing data to the server, the proposer utilizes cloud computing as data storage and distribution.…”
Section: Methodsmentioning
confidence: 99%
“…In [17], the authors introduced a system that notified the users when the trash bin is full. To build this autonomous system, the authors used Arduino UNO with ultrasonic sensors, and to control the bin they used servomotors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LMS is a system that carries out learning management such as identifying, assessing, tracking progress, and collecting assignments like Baumgartner's face-to-face classroom learning. Muhardi et al [5] Research revealed that LMS is an online learning solution due to limited time, place and meetings between students and teachers because it can be done outside the classroom. In addition, with the LMS the interaction between teachers and students is increasing.…”
Section: Introductionmentioning
confidence: 99%